Effects of heat shocks, heat waves, and sustained warming on solitary bees - Vilchez-Russell, Kaleigh A.; Rafferty, Nicole E. (Frontiers in Bee Science, 2024)
Along with higher average temperatures, global climate change is expected to lead to more frequent and intense extreme heat events, and these different types of warming are likely to differ in their effects on bees. Although solitary bees comprise >75% of bee species, and despite their ecological and economic value as pollinators, a literature search revealed that only 8% of studies on bee responses to warming involve solitary bees. Here we review studies that have addressed how solitary bees are affected by three main types of warming that vary in magnitude and duration: heat shocks, heat waves, and sustained warming. We focus on direct physiological and behavioral effects of warming on solitary bees, rather than the underlying mechanisms. We find that heat shocks have received little attention in solitary bees both in terms of number of studies and relative to social bees, and all of those studies examine the effects of heat shocks on a single genus, Megachile. This work has shown that heat-shocked eggs, larvae, and pupae tend to upregulate heat shock protein genes, while heat shock at the adult stage can increase mortality in male bees, potentially altering population sex ratios. We find that solitary bee responses to heat waves have received even less study, but the few studies suggest that these events can increase larval mortality and slow development time, and that bees may not be able to physiologically acclimate to heat wave conditions by increasing their critical thermal maxima. Finally, sustained warming, which has been relatively well-studied in solitary bees, can speed development rate, reduce body mass, increase mortality, and alter foraging behavior. Our review reveals knowledge gaps in the effects of heat shocks and heat waves on solitary bees and, more broadly, in the responses of unmanaged solitary bees to warming. To improve our ability to anticipate the consequences of climate change for these critical pollinators, we encourage research on solitary bee thermal responses that examines short-term, extreme warming and incorporates greater ecological realism and complexity.